Design improvement of air deployable parachute for high altitude launch ofpayload based on investigationand experimentation - Pratap M.; Agrawal A.K.; Sati S.C.; Saxena A.K. (My University, 2025)
Purpose: The purpose of this paper is to improve the design of a solid square canopy of a parachute. The design improvements are brought out by providing minor slits in the canopy area. Proper designing of the parachute was carried out using theoretical investigation coupled with experimentation. This parachute is designed for launch of sonobuoy from fixed wing aircraft. Design/methodology/approach: Literature review was carried out on the design of such parachutes for the launch of a sonobuoy from a high altitude to the water entry. Computational fluid dynamics (CFD) analysis provided the value of the coefficient of drag for the slit-cut square canopy parachute, with and without sonobuoy for different lengths of the slit. Besides the theoretical investigation, experimentation was also carried out to validate the design. Findings: The experimentation was carried out on 58 and 75 gsm fabric canopies with the slit edge plain-cut with thermally sealed edges, stitched and strengthened. In the case of plain-cut slits on the canopy made of 75 gsm fabric, no tearing of the slit edge was observed in dynamic and flight tests. Research limitations/implications: The present work has been carried out considering various assumptions and limited trial data specific to precision drop of 9 kg payload. The work can be adopted for bigger parachute for dropping of higher payloads. Originality/value: Lab strength test, track dynamic and flight trials were conducted to acquire useful data for the present analysis. Besides the theoretical investigations and CFD analysis inherently based on numerous assumptions, experimentation was carried out as the sonobuoy deployment conditions are full of uncertainty. Dynamic and airdrop tests were conducted for this reason to determine design changes in the slits, both at the material level and on improvisations. © 2021, Emerald Publishing Limited.